Early Spring Feeding Habits of Bearded Seals (Erignathus Barbatus) in the Central Bering Sea, 1981 - Antonelis, George A.; Melin, Sharon R.; Bukhtiyarov, Yurii A. (ARCTIC, 1994)
The diet of bearded seals, Erignathus barbatus, near St. Matthew Island, Bering Sea, was studied during the early spring of 1981. Eighty-six percent of the 78 seals' stomachs examined contained fish. Other prey taxon groups, in decreasing order of their percentages of occurrence, were crabs (73%), clams (55%), snails (47%), amphipods (32%), shrimp (18%), mysids (13%), marine worms (13%) and cephalopods (4%). The most frequently occurring prey species were capelin, Mallotus villosus, (82%); codfishes, Gadidae (64%); narrow snow crab, Chionoecetes opilio (63%); eelpouts, Lycodes spp. (56%); longsnout prickleback, Lumpenella longirostris (49%); nutshell clams, Nuculana sp. (42%); and moon snails, Polinices sp. (27%). Seventy-seven percent of the seals examined had consumed prey from three or more different taxon groups. We identified seven food items not previously reported as prey of the bearded seal in the Bering Sea. No differences were detected between the diets of males and females and between adults and juveniles, indicating no apparent segregation of foraging by sex or age. Bearded seals in the St. Matthew Island region of the Bering Sea forage in a manner similar to their conspecifics in other areas where fish constitute a major portion of their diet. Prey selection is probably dependent on availability, and diet may be highly diversified even within a relatively small area during a short period of time. Variety in prey consumption exemplified the ability of the bearded seal to forage in the seasonally changing habitat associated with the advance and retreat of the ice front.Key words: bearded seal, Erignathus barbatus, diet, demersal and pelagic fish, benthic invertebrates, prey species diversity On a étudié le régime alimentaire du phoque barbu, Erignathus barbatus, près de l'île Saint Matthew dans la mer de Béring, tôt au printemps de 1981. Quatre-vingt six p. cent des 78 estomacs de phoques examinés contenaient du poisson. Parmi les autres groupes de taxons servant de proies, on retrouvait, par ...